Prodicus at the Crossroads. Once Again on the Antilogy - Giombini, Stefania (Peitho. Examina Antiqua, 2017)
The aim of this paper is to analyze the tale of Heracles at the Crossroads, attributed to Prodicus by Socrates in Xenophon’s Memorabilia, through the notion of antilogy. The apologue has got an antilogic structure that is immediately outlined in the description of the situation in which the young Heracles finds himself. But the text, seemingly antilogic, does not develop itself according to one of the most important rules of antilogies, i.e., the epistemic parity of two speeches, since it appears to be completely in favor of just one of the theses. Prodicus would have had no interest in writing a text that did not demonstrate his rhetorical and linguistic abilities. According to this perspective, Xenophon’s version of Heracles at the Crossroads does not seem to be the original version by Prodicus, as can be seen by analyzing its structure and properties.